Diagnóstico de problemas organizacionales dentro de los grupos meta, como impulso para la sostenibilidad local en la parroquia El Tingo, Cantón Pujilí 2019 - Navarro Tapia, Jhonny Daniel (2020)
The present investigation is based on a diagnosis through the application of tools for the collection of primary or base line information such as the surveys and the matrices of those involved with stakeholder maps, in which they show the existing organizational failures within the associations the El Tingo La Esperanza parish in Canton Pujilí, focusing on their actions in the territory and their interaction with governmental and non-governmental organizations, in the same way the relationship between them within the physical space and their function as actors of territorial development, promoting economic flow and as a result territorial development. In this way, results and analysis focused on the target groups that excel within the parish were obtained as entities of improvement, qualifying as primary development groups, becoming involved in being organizations that contribute to the execution of the proposal to develop a federation of associations of the parish with the same purposes, objectives and a set of activities to promote their actions in front of the corresponding agencies such as Ministries, GADs and ONGs. Promoting the transformation of organizations into institutions with greater representativeness in agricultural, agro-industrial and organizational strengthening activities that expedite the economic development of the esperanceños families; being thus they happen to be actors of their own transformation.